Rumen Microbiology - Kamra, D. N.; Agarwal, Neeta; Chaudhary, L. C. (Indian Farming, 2015)
In the Rumen Microbiology Laboratory of Animal Nutrition Division at IVRI, research was started on use of microbial feed addtives in livstock in the early nineties. Besides this, research work goes on other aspects of rumen microbiology. Efforts are needed to investigate microbial diversity by metagenomics so as to elucidate essential microbial profile needed for optimum degradation of lignocellulosic feed digestion and reducing methane emission by the ruminants.